2015
DOI: 10.1016/j.fitote.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

First identification of natural products from the African medicinal plant Zamioculcas zamiifolia — A drought resistant survivor through millions of years

Abstract: Zamioculcas zamiifolia, an unusually drought resistant medicinal plant native to tropical east Africa and subtropical southeast Africa, including the countries Kenya, Malawi, Mozambique, South-Africa, Tanzania and Zimbabwe, is described as a living fossil which may have evolved as early as 42 million years ago. It belongs to the notoriously toxic family Araceae giving it, through association, a reputation for being toxic; despite little or no systematic evidence exists to support this claim. As an ancient plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
(22 reference statements)
0
6
0
1
Order By: Relevance
“…The SI values for each extract toward each cancer cell line were less than three, except for chloroform extract toward T47D cell line (Table 3). Previous study, the leaf extract of Z. zamiifolia and its isolated compounds were not toxic against brine shrimp Artemia salina [5] . Based on these results, it can be suggested that Z. zamiifolia is safe to be utilized as an ornamental plant.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The SI values for each extract toward each cancer cell line were less than three, except for chloroform extract toward T47D cell line (Table 3). Previous study, the leaf extract of Z. zamiifolia and its isolated compounds were not toxic against brine shrimp Artemia salina [5] . Based on these results, it can be suggested that Z. zamiifolia is safe to be utilized as an ornamental plant.…”
Section: Resultsmentioning
confidence: 83%
“…It seems that polyphenolics and flavonoids are the main compounds in semipolar and polar extracts. Previously, some flavonoids and polyphenolics were isolated from the extract of Z. zamiifolia leaves [5] . Thus, the similar compounds might be found from the roots of Z. zamiifolia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…benzoic, gallic, p ‐coumaric, ferulic, hydroxyferulic, sinapic) acid groups 5,6 . Flavones (O‐linked) acylated by 3‐hydroxy‐3‐methylglutaryl (HMG) have been reported from several families, 7 and HMG‐glycosyl flavones (C‐linked) have been reported in the Poaceae 8 , Leguminosae 9,10 and Araceae families 11 . However, HMG‐diglycosyl species (C‐linked) have rarely been reported, with the first report of vicenin‐II acylated by HMG being in 2014 from a TCM formula called Gui‐Zhi‐Tang 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Zamioculcas zamiifolia, of African origin, is widely used in landscape projects. This herbaceous plant from tropical regions belongs to the family Araceae, and grows to a height of 45-60 cm (Moullec et al, 2015). One of the main characteristics that has attracted the attention of producers is its good adaptability to low-light environments, in addition to exhibiting durability and tolerance to transport (Khaksar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%